Pengaruh Perubahan Musim Terhadap Pendapatan Nelayan - Rini Lukum; Radia Hafid; Melizubaida Mahmud (State University of Gorontalo, 2023)
The method used in this study was a quantitative method, with a total sample of 64 people. Besides the data collection techniques used questionnaires and documentation. The analysis results of the coefficient of determinatiom depicted that the adjusted coefficient of determination or the R-Square value was 0.174 or 17.4%. this value indicated that 17.4% of the variability of fishermen’s income could be explained by the seasonal change variable, while the remaining 82.6% was explained by other variables that were not examined in this study. The finding in the previous subsection found that the seasonal changes had a significant positive effect on the fishermen’s income in Leato Selatan Village, Gorontalo City. This result was proven by the t-count value of 6.181, whieh was higher than t-table value of 1.999897 and the significance value was 0.000 or less than 0.05. these signified that seasonal change affected the fishermen’s income in Leato Selatan Villange, Gorontalo City.